Applications of Pyrrole Based Molecularly Imprinted Polymers as Analytical Sensors: a Review - Rajendraprasad,Nagaraju (2022)
Abstract Molecularly imprinted polymers (MIPs) are an important class of compounds with wider sensing applications for the determination of substances ranging from small molecular masses to macro size. The hyphenation of MIP principle with other likewise conducting polymers yields the devices for sensing purposes. MIPs are robust against environmental conditions, more economical than natural receptors, and their preparation is also adequate for substances without natural receptors. Organic mediated MIPs compounds are of current interest, due to their applicability as quantification tools to determine electroactive substances in a variety of real samples. MIPs are highly selective for target molecules, mechanically strong, resistant to temperature and pressure, inert towards acids, bases, metal ions and organic solvents, highly stable for longer periods, and operative at room-temperature. Therefore, during past years, MIPs have been used as electrochemical and optical sensors, sorbents, solid phase media, and so on. Herein, there is a focus on the use of Pyrrole (Py) as a monomeric molecule to fabricate MIPs. Py or poly-Py (p-Py) based MIPs are synthesized and used in various capacities as chemo electrochemical sensors. A detailed discussion on the application of Py-mediated MIPs for the electrochemical determination of some organic compounds of therapeutic and environmental interest is herein presented as a review.